Cholangiopathy with Respect to Biliary Innate Immunity - Kenichi Harada; Yasuni Nakanuma (International Journal of Hepatology)
Biliary innate immunity is involved in the pathogenesis of cholangiopathies in cases of biliary disease. Cholangiocytes possess Toll-like receptors (TLRs) which recognize pathogen-associated molecular patterns (PAMPs) and play a pivotal role in the innate immune response. Tolerance to bacterial PAMPs such as lipopolysaccharides is also important to maintain homeostasis in the biliary tree, but tolerance to double-stranded RNA (dsRNA) is not found. Moreover, in primary biliary cirrhosis (PBC) and biliary atresia, biliary innate immunity is closely associated with the dysregulation of the periductal cytokine milieu and the induction of biliary apoptosis and epithelial-mesenchymal transition (EMT), forming in disease-specific cholangiopathy. Biliary innate immunity is associated with the pathogenesis of various cholangiopathies in biliary diseases as well as biliary defense systems.